Analisis Kinerja Polisi Kehutanan Unit Pelaksana Teknis Taman Nasional Bukit Duabelas dalam Perlindungan dan Pengamanan Kawasan - Putra, Ardiyansyah; Hidayat, Rahmat; Jayanegara, Oscar (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
Forest Ranger is one of the functional positions tasked with carrying out Forest Police activities, including preparing, implementing, developing, monitoring, evaluating, and reporting on forest protection and security activities, forest area protection, and supervision of the distribution of forest products. This research aims to analyze and describe the performance of forest police in the context of area protection and security and to design strategies to enhance the performance of Forest Police at Bukit Duabelas National Park. This research uses a descriptive qualitative approach. Data collection techniques include observation, interviews, and documentation. Sampling is done purposively, and data analysis techniques include data collection, data reduction, data presentation, and conclusions. The results of this study indicate that in carrying out area protection and security activities, forest ranger adjust individual performance targets with organizational performance targets outlined in pre-emptive and preventive security activities which have succeeded in reducing area disturbances such as encroachment and Illegal Logging. Encroachment disturbance is dominant in the Bukit Duabelas National Park Region II Tebo Management Section, while Illegal Logging disturbance is dominant in the Bukit Duabelas National Park Region I Batanghari Management Section. Strategies to improve the performance of forest police in area protection and security include: (1) Increasing Capability, (2) Improving Skills, (3) Enhancing Knowledge, (4) Improving Attitudes, (5) Boosting Motivation, and (6) Managing Stress.